Efektivitas Konseling Kelompok Dengan Teknik Thought Stopping Untuk Mereduksi Kecanduan Judi Koprok - Reni Marisa; Komaruddin Komaruddin; Lena Marianti (Journal of Society Counseling, 2023)
The background of this research is that the fathers in Sindang Marga village are very obsessed with the koprok gambling game, that those who do koprok gambling actually do not only fulfill the economy, but they think that by doing this gambling they can improve their standard of living with small capital and get profits. the big ones seem to have to work hard. This study examines the "Effectiveness of group counseling with the Thought Stopping technique to reduce koprok gambling addiction in Sindang Marga Village, Sungai Keruh District, Musi Banyuasin Regency." The research objectives were to determine koprok gambling behavior among adult men and to determine the effectiveness of group counseling with the Thought Stopping technique to reduce koprok gambling behavior among adult men in Sindang Marga Village, Sungai Keruh District, Musi Banyuasin Regency. The research methodology used in this study is quantitative and experimental research in the form of a One-Group Pretest-Posttest Design. In this study, there were 7 samples using data analysis techniques through validity, reliability, Wilcoxon tests. The results of the study (1) Koprok gambling behavior among adult men in Sindang Marga Village can be seen from the results of the frequency descriptive analysis test, the response value of respondents was obtained as many as 28 gentlemen stated that the percentage value of 79.42% (mean) was in the very high category, this is proves that koprok gambling behavior is formed due to compulsive behavior, dependence and difficulty to control themselves because the koprok gambling game thinks they will get additional benefits or money if they win the gambling game, whereas in reality the koprok gambling players only spend time, skip prayer time to show excessive anger towards the family when reprimanding them for playing koprok gambling in Sindang Marga Village. (2) obtained from the Wilcoxon test = Asymp.sig (2-tailed) is 0.000. Value 0.01 < 0.05, it can be concluded that Ha is accepted and H0 is rejected, which means that group counseling with the Thought Stopping technique is effectively used to reduce koprok gambling addiction among adult men.